Data-assimilated lifecycle simulation for adaptive product lifecycle management. Issue 1 (2017) - Fukushige, Shinichi; Nishioka, Masaki; Kobayashi, Hideki
Abstract: This paper proposes a data-assimilated lifecycle simulation (DA-LCS) system. Data assimilation (DA) is a self-adjustment method for decreasing differences between a simulation and observation data from an actual-system by conforming the simulation model parameters to the observation at appropriate time intervals. The proposed system applies DA to LCS for adaptive operations in product lifecycle management. A case study of the lifecycle of a photovoltaic panel reuse business shows that DA-LCS successfully merges measurement data acquired from actual business operations into the LCS model, and sequentially revises the simulation estimations through DA.